1982
DOI: 10.1172/jci110558
|View full text |Cite
|
Sign up to set email alerts
|

3 alpha, 17 beta-androstanediol glucuronide in plasma. A marker of androgen action in idiopathic hirsutism.

Abstract: A B S T R A C T Biologically active androgens and peripheral androgen metabolites in plasma were measured in 25 women with idiopathic hirsutism (IH). Plasma testosterone was not significantly elevated. Free testosterone however was increased although the elevation was not impressive (10.9±6.6 SD vs. 3.3±1.5 ng/dl) and one-fourth of the cases had normal unbound testosterone. Dihydrotestosterone (DHT) values were elevated (23.5±14 vs. 12.5±3.59) but again over half of the values were within the normal range. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
3

Year Published

1986
1986
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(55 citation statements)
references
References 28 publications
8
44
3
Order By: Relevance
“…However, androgens did not change after surgery to a significant degree within the first 8 weeks after surgery, consistent with previous reports on ‘normal’ levels in BPH and PCa patients [15, 16, 17], on the lack of correlation with PSA values [18, 19], and on unaltered serum androgens after removal of adenomas [20]. Furthermore, 3α,17β–androstanediol glucuronide, a DHT metabolite and marker of androgen action [21], was not significantly altered in men developing PCa [22]. …”
Section: Discussionsupporting
confidence: 88%
“…However, androgens did not change after surgery to a significant degree within the first 8 weeks after surgery, consistent with previous reports on ‘normal’ levels in BPH and PCa patients [15, 16, 17], on the lack of correlation with PSA values [18, 19], and on unaltered serum androgens after removal of adenomas [20]. Furthermore, 3α,17β–androstanediol glucuronide, a DHT metabolite and marker of androgen action [21], was not significantly altered in men developing PCa [22]. …”
Section: Discussionsupporting
confidence: 88%
“…RIA measurements of 5α-androstan-3α,17β-diol glucuronide levels revealed that this metabolite was also present at background levels in the sera of type 2-deficient and type 1-and 2-deficient mice. This steroid is produced from DHT by reductive 3α-hydroxysteroid dehydrogenases, and its presence in the plasma of humans is directly proportional to the level of DHT (34)(35)(36). Inasmuch as these findings translate to the mouse, the absence of 5α-androstan-3α,17β-diol glucuronide from the knockout animals suggests that circulating levels of DHT are, in fact, very low or absent.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, clear alterations of the androgen profile in serum have been described in adult women with hirsutism. Horton et al [27]have demonstrated elevated 3α-androstanediol glucuronide and free testosterone serum levels in 25 women when compared to those determined in 16 normal women. Therefore, they propose that 3α-androstanediol glucuronide is a reliable serum marker of peripheral androgen action.…”
Section: Discussionmentioning
confidence: 99%